Contingent reserves management: An applied framework - Ricardo Caballero; Stavros Panageas (Federal Reserve Bank of Boston, 2005)
One of the most serious problems that a central bank in an emerging market economy can face is the sudden reversal of capital inflows. Hoarding international reserves can be used to smooth the impact of such reversals, but these reserves are seldom sufficient and always expensive to hold. In this paper we argue that adding richer hedging instruments to the portfolios held by central banks can significantly improve the efficiency of the anti?sudden stop mechanism. We illustrate this point with a simple quantitative hedging model, where optimally used options and futures on the S&P100's implied volatility index (VIX) increases the expected reserves available during sudden stops by as much as 40 percent.
Keywords: E2; E3; F3; F4; G0; C1; 330; Sudden stops; reserves; portfolio; VIX; hedging; options; futures; Währungsreserven; Zentralbank; Portfolio-Management; Aufstrebende Märkte; Theorie